The edge of nowhere - George, Elizabeth 1949- (New York Viking, 2012)
When her mother abandons her on Whidbey Island, Washington, a fourteen-year-old girl with psychic abilities meets a Ugandan orphan with a secret.
Keywords: Psychic ability -- Fiction; Abandoned children -- Fiction; Secrets -- Fiction; Whidbey Island (Wash.) -- Fiction